2013
DOI: 10.1108/aeat-feb-2012-0027
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on effect of leading‐edge tubercles

Abstract: PurposeThe purpose of this paper is to investigate the effect of spanwise shape of the leading edge on unsteady aerodynamic characteristics of wings during forward flapping and gliding flight.Design/methodology/approachA computational fluid dynamics approach was conducted to analyze the flow around airfoils with sinusoidal‐like protuberances at a Reynolds number of 104. Three‐dimensional time‐dependent incompressible Navier‐Stokes equations are numerically solved by using finite volume method. A multigrid mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…1 After this early morphological investigation, many studies attempted to demonstrate the feasibility of leading edge serrations as passive flow control devices for wings to quantify the magnitude of any benefit that they may offer. [2][3][4][5][6][7][8][9][10][11][12][13][14] All the studies concerning the effect of leading edge serrations on airfoil performance draw a consensus that the serrations can delay the stall occurrence, increase post-stall lift, decrease post-stall drag and reduce the laminar separation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…1 After this early morphological investigation, many studies attempted to demonstrate the feasibility of leading edge serrations as passive flow control devices for wings to quantify the magnitude of any benefit that they may offer. [2][3][4][5][6][7][8][9][10][11][12][13][14] All the studies concerning the effect of leading edge serrations on airfoil performance draw a consensus that the serrations can delay the stall occurrence, increase post-stall lift, decrease post-stall drag and reduce the laminar separation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…However, under post stall conditions, the lift had recovered, and increased coverage by the undulations ultimately led to increased performance. Recently, Xingwei et al [14] performed a Reynolds-averaged study of wings with a sinusoidal leading edge during forward flapping and gliding flight. Webber et al Favier et al [17] conducted direct numerical simulations of an undulating geometry at low Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…A pitching study by Wang et al [51] found a negligible change in performance in tubercled designs, although foil geometry was quite different than [12], and Re was an order of magnitude greater. In contrast, a study by Zhang et al [52] revealed potential advantages for tubercled leading edges during flapping flight.…”
Section: Plos Onementioning
confidence: 88%